2012
DOI: 10.1590/s1413-70542012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enzymatic hydrolysis and lactic fermentation to obtain a yogurt with low lactose content

Abstract: In a single-stage process with the simultaneous addition of β -galactosidase and lactic culture, the lactose conversion, the processing time, viscosity and syneresis were evaluated. Fermentation was promoted by lactic culture containing two probiotic microorganisms, Bifidobacterium animalis and Lactobacillus acidophilus, associated with the typical microorganisms of yogurt.An enzymatic preparation containing β -galactosidases from Kluyveromyces lactis and Aspergillus niger was used. , enzyme concentration of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…This could be due to greater activity of traditional yogurt cultures at typical yogurt pH value. Similar data were found by Batista and others () and Martins and others (). In general, there was a significant decrease in lactose content as a function of storage time linked to ability by starter bacteria to produce lactic acid.…”
Section: Resultssupporting
confidence: 92%
“…This could be due to greater activity of traditional yogurt cultures at typical yogurt pH value. Similar data were found by Batista and others () and Martins and others (). In general, there was a significant decrease in lactose content as a function of storage time linked to ability by starter bacteria to produce lactic acid.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, some studies reported GOS synthesis in the preparation of traditional yogurts. The authors attributed this finding to the LAB and bifidobacteria cultures employed, reaching concentrations from 0.08 to 1.35 g L −1 . Likewise, Song et al detected β ‐galactosidase hydrolytic activities by LAB strains currently used in yogurt making ( L. acidophilus , Lactococcus lactis , Lactobacillus helveticus and Lactobacillus paracasei ); besides, they found that L. paracasei had the highest hydrolytic activity and good ability to synthesize GOS in reconstituted whey powder.…”
Section: Resultsmentioning
confidence: 96%
“…Damin et al (2009) also found increases in the time to reach pH 4.6 with increases in SMP and WPC levels for yogurts supplemented. Meanwhile, Martins et al (2012) reported processing time slightly higher for yogurts prepared from milk fortified with WPC.…”
Section: Physicochemical Parameters Fermentation Time and Microbiolmentioning
confidence: 99%
“…After 8 h of incubation at 41°C, they achieved lactose values between 0.2 and 2.5 g.100 mL −1 , and values of glucose and galactose between 1.0-3.0 and 1.6-3.8 g.100 mL −1 , respectively. In turn, most recently, Martins et al (2012) obtained yogurts with 0.20 g.100 mL −1 of lactose using a milk base with 13.5% (w/w) of total solids and 9.1 g.100 mL −1 of lactose, prepared from whole milk powder and whey powder. The enzymatic catalysis was promoted by a mix of β-galactosidases from K. lactis and A. niger, and the lactic fermentation was carried out at 43°C for approximately 3.50 h using a commercial starter containing the typical yogurt cultures together with two probiotic bacteria (B. animalis and L. acidophilus).…”
Section: Glucose and Galactosementioning
confidence: 99%